Doping in Racing Pigeons (Columba livia domestica): A Review and Actual Situation in Belgium, a Leading Country in This Field - Didier Marlier (Veterinary Sciences, 2022)
Pigeon racing is a sport in which trained homing pigeons (Columba livia domestica) are released between 60 and 1200 km from their loft and then have to return home as quickly as possible. The first race was held in 1818 in Belgium and since then, Belgium has led the world in pigeon breeding. Unfortunately, as in other sports, doping has become a major issue and doping controls have been implemented. This review provides information about pigeon racing, rules from the Royal Federation Colombophile of Belgium, and laws applicable in Belgium as doping control issues cannot be understood without including them as part of pigeon racing. The main pharmacological data concerning corticoids, non-steroidal anti-inflammatory drugs, anabolic steroids, pain relievers and narcotic analgesics, bronchodilators and β-agonists, drugs acting on the central nervous system and other performance-enhancing drugs, in addition to methods relevant to doping in pigeons are presented. Moreover, the chosen matrix and analytical methods are described.